Histological Disorganization of Spleen Compartments and Severe Visceral Leishmaniasis - Hermida, Micely d'El-Rei; de Melo, Caroline Vilas Boas; Lima, Isadora dos Santos; Oliveira, Geraldo Gileno de Sá; dos-Santos, Washington L. C. (Frontiers in Cellular and Infection Microbiology, 2018)
The spleen is a secondary lymphoid organ responsible for immune surveillance against blood-circulating pathogens. Absence of the spleen is associated with increased susceptibility to systemic spread and fatal infection by different pathogens. Severe forms of visceral leishmaniasis are associated with disorganization of spleen compartments where cell interactions essential for splenic immunological function take place. White pulp atrophies, secondary lymphoid follicles and marginal zones vanish, and the boundaries separating white and red pulp blur. Leukocyte populations are reduced or disappear or are replaced by plasma cells. In this paper, we review the published data on spleen disorganization in severe forms of visceral leishmaniasis and propose a histological classification to help the exchange of information among research groups.